Correction: Ab initio and empirical defect modeling of LaMnO3±δ for solid oxide fuel cell cathodes. Issue 11 (24th February 2016) - Lee, Yueh-Lin; Xu, Shenzhen; Morgan, Dane
Abstract : Correction for ' Ab initio and empirical defect modeling of LaMnO3± δ for solid oxide fuel cell cathodes' by Yueh-Lin Lee et al., Phys. Chem. Chem. Phys., 2012, 14, 290–302.